Column sealing material, method of making and use thereof
Patent Information
- Application Number
- CN202512056334.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-31
- Publication Date
- 2026-10-27
AI Technical Summary
[0005]本发明的目的是为了克服现有泄漏检测传感器在石化生产苛刻环境下存在的灵敏度低,稳定性、耐候性、抗静电性以及机械强度差的问题,提供一种塔器密封材料及其制备方法和应用
[0020]本发明所述的塔器密封材料包括热塑性聚酯弹性体、热塑性聚酰胺弹性体、光稳定剂以及可选的纳米碳材料;所述热塑性聚酯弹性体作为基体,所述塑性聚酰胺弹性体作为抗静电改性剂,辅以双重光稳定剂耐候体系,并集成纳米导电功能与纳米增强结构,使得所述塔密封材料不仅具有良好的导电性能、优异的力学特性、出色的抗老化性能,还具有优异的气密性。非常适合用于石化行业塔器密封微小泄漏高分辨高精度传感器体系的密封材料,以确保高精度传感器的稳定性和准确性,具有广阔的应用前景和产业化价值。此外,本发明所述的制备方法相对简单,生产设备要求低且施难度低,便于实现工业化生产制造。
Smart Images

Figure CN122978656A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of sealing materials technology, specifically to a tower sealing material, its preparation method, and its application. Background Technology
[0002] my country's petrochemical industry has experienced sustained and rapid development in recent years. Its main product capacity, new investment, and chemical sales have all ranked first in the world. The concentration of petrochemical production has increased significantly, and the industry's technological level and core competitiveness have continuously improved. However, major fire and explosion accidents still occur frequently in my country in recent years. The large-scale, intensive, and industrial park-based development of the petrochemical industry has led to the accumulation of safety risks and a surge in domino-effect risks. Statistics show that accidents caused by leaks in typical petrochemical equipment such as storage tanks, pipelines, and towers account for more than 42% of all accidents. However, existing leak detection sensors still suffer from technical bottlenecks such as low sensitivity and poor stability in the harsh environment of petrochemical production. There is an urgent need to develop new leak sensors for storage tanks, pipelines, and towers adapted to this scenario, solving the problem of equipment-level leak detection, improving the early warning level of the national-level intelligent safety risk management platform, and effectively preventing and mitigating major safety risks.
[0003] As a core component of the sealing structure of novel sensors, the performance of sealing materials directly determines the sealing reliability and leakage prevention capabilities of the sensors. Under the harsh operating conditions of petrochemical production, sealing materials must withstand long-term erosion from high temperatures, high pressures, and highly corrosive media, and also possess excellent deformation compensation capabilities and anti-aging properties in order to effectively block media leakage channels and ensure stable operation of the sensor in complex environments.
[0004] Therefore, in response to the urgent need for high-performance industrial sensors for leak monitoring of critical equipment in the harsh environment of petrochemical production, and the technical pain point that multiphase media leakage in tower sealing parts is difficult to measure directly, the design and preparation of special sealing materials adapted to high-resolution, high-precision sensor systems for micro-leakage in tower sealing, based on the core requirements of the harsh environment and complex service conditions of petrochemical production, has become a major technical problem that urgently needs to be solved. Summary of the Invention
[0005] The purpose of this invention is to overcome the problems of low sensitivity, poor stability, weather resistance, antistatic properties, and poor mechanical strength of existing leak detection sensors in the harsh environment of petrochemical production, and to provide a tower sealing material, its preparation method, and its application. The tower sealing material includes thermoplastic polyester elastomers, thermoplastic polyamide elastomers, light stabilizers, and optional nano-carbon materials, possessing excellent weather resistance, antistatic properties, mechanical strength, and hydrogen barrier properties, making it suitable for use in high-precision leak sensor systems.
[0006] To achieve the above objectives, the present invention provides a tower sealing material comprising a thermoplastic polyester elastomer, a thermoplastic polyamide elastomer, a light stabilizer, and optional nano-carbon materials; wherein the weight ratio of the thermoplastic polyester elastomer to the thermoplastic polyamide elastomer is 2-15:1.
[0007] Preferably, based on the total weight of the tower sealing material, the tower sealing material contains 50-90 wt% of the thermoplastic polyester elastomer, 5-40 wt% of the thermoplastic polyamide elastomer, 0.1-10 wt% of the light stabilizer and 0-5 wt% of the nano-carbon material.
[0008] Preferably, the weight ratio of the thermoplastic polyester elastomer to the thermoplastic polyamide elastomer is 2.5-12:1.
[0009] Preferably, the hardness of the thermoplastic polyester elastomer is 20-80D.
[0010] Preferably, the thermoplastic polyamide elastomer is selected from at least one of polyether block amide, polyester block amide, and polysiloxane block amide.
[0011] Preferably, the light stabilizer is a combination of benzotriazole light stabilizers and hindered amine light stabilizers, and the weight ratio of the benzotriazole light stabilizer to the hindered amine light stabilizer is 1:0.1-10.
[0012] Preferably, the benzotriazole light stabilizer is selected from at least one of 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-5-chlorobenzotriazole, 2'-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole, and 2,2'-methylene-bis[4-tert-octyl-6-(2H-benzotriazolyl-2)]phenol.
[0013] Preferably, the hindered amine light stabilizer is selected from at least one of bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate, poly[1-(2-hydroxyethyl)-2,2,6,6-tetramethyl-4-hydroxypiperidinyl succinate] and poly{[6-[(1,1,3,3-tetramethylbutyl)amino]]-1,3,5-triazine-2,4-[(2,2,6,6-tetramethyl-piperidinyl)imino]-1,6-hexamethylene[(2,2,6,6-tetramethyl-4-piperidinyl)imino]}.
[0014] Preferably, the nano-carbon material is selected from at least one of multi-walled carbon nanotubes, graphene, reduced graphene oxide, and carbon fiber.
[0015] A second aspect of the present invention provides a method for preparing the above-mentioned tower sealing material, the method comprising the following steps:
[0016] (1) The thermoplastic polyester elastomer is mixed with the thermoplastic polyamide elastomer, and then the resulting mixture, the light stabilizer and the optional nano-carbon material are mixed together;
[0017] (2) The material obtained in step (1) is added to a twin-screw extruder for extrusion and granulation to obtain granules. The granules are then injection molded, demolded, and sized.
[0018] Preferably, in step (2), the temperatures of the seven heating zones of the twin-screw extruder are set as follows: Zone 1: 140-160℃, Zone 2: 160-170℃, Zone 3: 170-180℃, Zone 4: 180-190℃, Zone 5: 190-200℃, Zone 6: 200-205℃, and Zone 7: 200-205℃.
[0019] The third aspect of this invention provides the application of the above-mentioned tower sealing material in a high-resolution, high-precision sensor system for minor leaks in tower sealing.
[0020] The tower sealing material of this invention comprises thermoplastic polyester elastomer, thermoplastic polyamide elastomer, light stabilizer, and optional nano-carbon materials. The thermoplastic polyester elastomer serves as the matrix, the thermoplastic polyamide elastomer as an antistatic modifier, and a dual light stabilizer weather-resistant system is incorporated. Furthermore, it integrates nano-conductive functionality and a nano-reinforcing structure, resulting in a tower sealing material that not only possesses excellent electrical conductivity, superior mechanical properties, and outstanding anti-aging performance, but also excellent airtightness. It is highly suitable for use as a sealing material in high-resolution, high-precision sensor systems for sealing towers in the petrochemical industry to prevent minor leaks, ensuring the stability and accuracy of high-precision sensors. This material has broad application prospects and industrialization value. Moreover, the preparation method described in this invention is relatively simple, requires low-level production equipment, and is easy to implement, facilitating industrial-scale manufacturing. Attached Figure Description
[0021] Figure 1 Here is a scanning electron microscope image of the tower sealing material S4 prepared in Example 4;
[0022] Figure 2 These are test graphs showing the mechanical properties of the tower sealing material S5 prepared in Example 5 before and after aging.
[0023] Figure 3 These are test graphs showing the mechanical properties of the tower sealing material S6 prepared in Example 6 before and after aging.
[0024] Figure 4 This is a graph showing the thermogravimetric test results of the tower sealing material S3 prepared in Example 3. Detailed Implementation
[0025] The following provides a detailed description of specific embodiments of the present invention. It should be understood that the specific embodiments described herein are for illustrative and explanatory purposes only and are not intended to limit the scope of the invention.
[0026] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0027] The tower sealing material of this invention comprises thermoplastic polyester elastomer, thermoplastic polyamide elastomer, light stabilizer, and optional nano-carbon material. The weight ratio of the thermoplastic polyester elastomer to the thermoplastic polyamide elastomer is 2-15:1.
[0028] In this invention, the thermoplastic polyester elastomer (TPEE) can be a commercially available product or prepared using methods commonly found in the art. In some specific embodiments, the TPEE can be H605 commercially available from Sichuan Chenguang Kexin Plastics Co., Ltd., HYBRAR 512 commercially available from Kuraray Co., Ltd., or PELPRENE S-9001 commercially available from Toyobo Co., Ltd.
[0029] In some embodiments, the hardness of the thermoplastic polyester elastomer is 20-80D, preferably 26-75D.
[0030] In the tower sealing material, the thermoplastic polyamide elastomer acts as an antistatic modifier, increasing conductivity while enhancing toughness. Preferably, the thermoplastic polyamide elastomer is selected from at least one of polyether block amides, polyester block amides, and polysiloxane block amides. More preferably, the thermoplastic polyamide elastomer is a polyether block amide. As a specific example, the polyether block amide can be Pebax, commercially available from Arkema Group. 2533 or Rilsamid PA12.
[0031] In the tower sealing material, the light stabilizer can effectively improve the material's anti-aging properties. Preferably, the light stabilizer is a combination of a benzotriazole light stabilizer and a hindered amine light stabilizer, and the weight ratio of the benzotriazole light stabilizer to the hindered amine light stabilizer is 1:0.1-10, preferably 1:0.5-5, and more preferably 0.6-3.
[0032] In some preferred embodiments, the benzotriazole light stabilizer is selected from at least one of 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-5-chlorobenzotriazole, 2'-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole, and 2,2'-methylene-bis[4-tert-octyl-6-(2H-benzotriazolyl-2)]phenol. In a further preferred embodiment, the benzotriazole light stabilizer is 2'-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole (Tinuvin 326).
[0033] In some preferred embodiments, the hindered amine light stabilizer is selected from at least one of bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate, poly[1-(2-hydroxyethyl)-2,2,6,6-tetramethyl-4-hydroxypiperidinylsuccinate], and poly{[6-[(1,1,3,3-tetramethylbutyl)amino]]-1,3,5-triazine-2,4-[(2,2,6,6-tetramethyl-piperidinyl)imino]-1,6-hexamethylene[(2,2,6,6-tetramethyl-4-piperidinyl)imino]}. In a further preferred embodiment, the hindered amine light stabilizer is bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate (hindered amine light stabilizer 700).
[0034] In the tower sealing material, the nano-carbon material can improve the antistatic effect and enhance the material's mechanical properties. Preferably, the nano-carbon material is selected from at least one of multi-walled carbon nanotubes, graphene, reduced graphene oxide, and carbon fibers. More preferably, the nano-carbon material is multi-walled carbon nanotubes and / or reduced graphene oxide. As a specific example, the nano-carbon material can be multi-walled carbon nanotubes, reduced graphene oxide, or a combination of multi-walled carbon nanotubes and reduced graphene oxide.
[0035] The tower sealing material, based on its total weight, contains 50-90 wt% of the thermoplastic polyester elastomer, 5-40 wt% of the thermoplastic polyamide elastomer, 0.1-10 wt% of the light stabilizer, and 0-5 wt% of the nano-carbon material. Preferably, based on its total weight, the tower sealing material contains 60-89 wt% of the thermoplastic polyester elastomer, 6-35 wt% of the thermoplastic polyamide elastomer, 0.5-8 wt% of the light stabilizer, and 0.1-4 wt% of the nano-carbon material. More preferably, based on its total weight, the tower sealing material contains 69-88 wt% of the thermoplastic polyester elastomer, 8-30 wt% of the thermoplastic polyamide elastomer, 0.5-6 wt% of the light stabilizer, and 0.4-3 wt% of the nano-carbon material.
[0036] In some preferred embodiments, the weight ratio of the thermoplastic polyester elastomer to the thermoplastic polyamide elastomer is 2.5-12:1, more preferably 3-10:1. As specific examples, the weight ratio of the thermoplastic polyester elastomer to the thermoplastic polyamide elastomer can be 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, or 10:1.
[0037] In this invention, the thermoplastic polyester elastomer serves as the matrix, the plastic polyamide elastomer serves as the antistatic modifier, and a dual light stabilizer weathering system is added. Furthermore, the nano-conductive function and nano-reinforcing structure are integrated, so that the tower sealing material not only has good electrical conductivity, excellent mechanical properties, and outstanding anti-aging properties, but also excellent airtightness.
[0038] The present invention also provides a method for preparing the above-mentioned tower sealing material, the method comprising the following steps:
[0039] (1) The thermoplastic polyester elastomer is mixed with the thermoplastic polyamide elastomer, and then the resulting mixture, the light stabilizer and the optional nano-carbon material are mixed together;
[0040] (2) The material obtained in step (1) is added to a twin-screw extruder for extrusion and granulation to obtain granules. The granules are then injection molded, demolded, and sized.
[0041] In some preferred embodiments, step (1) specifically includes: mixing the plastic polyester elastomer and the thermoplastic polyamide elastomer until uniformly dispersed; then, further mixing the resulting mixture with the hindered amine light stabilizer and the benzotriazole light stabilizer until uniformly dispersed; and then adding the nano-carbon material and mixing until uniformly dispersed. In this invention, after adding the nano-carbon material, high-speed mechanical stirring can be used to ensure that the nano-carbon material is uniformly dispersed.
[0042] In some embodiments, the specific process of adding the material obtained in step (1) to a twin-screw extruder for extrusion granulation in step (2) includes: adding the material obtained in step (1) to a twin-screw extruder and performing melt extrusion at a temperature of 140-205℃ and a screw speed of 300-500rpm; then sequentially drawing, cooling, granulating, and drying the obtained melt extruded material to obtain uniformly mixed granules.
[0043] In some specific embodiments, in step (2), the seven heating zones of the twin-screw extruder are set to the following temperatures: Zone 1 140-160℃, Zone 2 160-170℃, Zone 3 170-180℃, Zone 4 180-190℃, Zone 5 190-200℃, Zone 6 200-205℃, and Zone 7 200-205℃.
[0044] The method described in this invention ensures the uniform dispersion of the nano-carbon material, the thermoplastic polyester elastomer, the thermoplastic polyamide elastomer, and the light stabilizer through an efficient mixing process. Based on this, a homogeneous material is obtained through twin-screw extrusion granulation. Through carefully designed component ratios and material selection, the high-performance sealing material of this invention not only ensures that the prepared composite material possesses good electrical conductivity, excellent mechanical properties, and outstanding anti-aging properties, but also excellent airtightness. Furthermore, the preparation method described in this invention is relatively simple, requires minimal production equipment, and is easy to implement, facilitating industrial-scale manufacturing.
[0045] This invention further provides the application of the aforementioned tower sealing material in a high-resolution, high-precision sensor system for minor leaks in tower seals. This material not only ensures that the prepared composite material possesses good electrical conductivity, excellent mechanical properties, and outstanding anti-aging properties, but also exhibits excellent airtightness. It is highly suitable as a sealing material for high-resolution, high-precision sensor systems for minor leaks in tower seals in the petrochemical industry, ensuring the stability and accuracy of high-precision sensors.
[0046] The following examples further illustrate the tower sealing material, its preparation method, and its application according to the present invention. These examples are implemented based on the technical solution of the present invention, providing detailed implementation methods and specific operating procedures; however, the scope of protection of the present invention is not limited to the following examples.
[0047] Unless otherwise specified, the experimental methods used in the following embodiments are conventional methods in the art. Unless otherwise specified, the experimental materials used in the following embodiments are commercially available.
[0048] In the following examples and comparative examples, TPEE was purchased from Sichuan Chenguang Kexin Plastics Co., Ltd., with grade H605 and hardness of 53D;
[0049] The thermoplastic polyamide elastomer was Pebax, purchased from Arkema Group. 2533;
[0050] Tinuvin 326 was purchased from BASF.
[0051] Multi-walled carbon nanotubes were purchased from Jiangsu Xianfeng Nanomaterials Technology Co., Ltd.
[0052] Reduced graphene oxide was purchased from Jiangsu Xianfeng Nanomaterials Technology Co., Ltd.
[0053] Example 1
[0054] (1) Mix 1800g of TPEE and 300g of Pebax evenly, then mix the resulting mixture with 20g of hindered amine light stabilizer 770 and 20g of Tinuvin 326 evenly, then add 40g of multi-walled carbon nanotubes and 20g of reduced graphene oxide, and mix until evenly dispersed.
[0055] (2) The material obtained in step (1) is added to a twin-screw extruder and melt-extruded at a temperature of 140-205℃ and a screw speed of 400rpm. Then the melt-extruded material is sequentially drawn, cooled, granulated and dried to obtain uniformly mixed granules. The granules are then injection molded, demolded and sized to obtain tower sealing material S1.
[0056] The seven heating zones of the twin-screw extruder are set with the following temperatures: Zone 1: 140-160℃; Zone 2: 160-170℃; Zone 3: 170-180℃; Zone 4: 180-190℃; Zone 5: 190-200℃; Zone 6: 200-205℃; and Zone 7: 200-205℃.
[0057] Example 2
[0058] (1) Mix 1700g of TPEE and 200g of Pebax evenly, then mix the resulting mixture with 20g of hindered amine light stabilizer 770 and 30g of Tinuvin 326 evenly, and then add 10g of multi-walled carbon nanotubes and mix until evenly dispersed.
[0059] (2) The material obtained in step (1) is added to a twin-screw extruder and melt-extruded at a temperature of 140-205℃ and a screw speed of 400rpm. Then the melt-extruded material is sequentially drawn, cooled, granulated and dried to obtain uniformly mixed granules. The granules are then injection molded, demolded and sized to obtain tower sealing material S2.
[0060] The seven heating zones of the twin-screw extruder are set with the following temperatures: Zone 1: 140-160℃; Zone 2: 160-170℃; Zone 3: 170-180℃; Zone 4: 180-190℃; Zone 5: 190-200℃; Zone 6: 200-205℃; and Zone 7: 200-205℃.
[0061] Example 3
[0062] (1) Mix 1800g of TPEE and 360g of Pebax evenly, then mix the resulting mixture with 60g of hindered amine light stabilizer 770 and 60g of Tinuvin 326 evenly, and then add 30g of reduced graphene oxide and mix until evenly dispersed.
[0063] (2) The material obtained in step (1) is added to a twin-screw extruder and melt-extruded at a temperature of 140-205℃ and a screw speed of 400rpm. Then the melt-extruded material is sequentially drawn, cooled, granulated and dried to obtain uniformly mixed granules. The granules are then injection molded, demolded and sized to obtain tower sealing material S3.
[0064] The seven heating zones of the twin-screw extruder are set with the following temperatures: Zone 1: 140-160℃; Zone 2: 160-170℃; Zone 3: 170-180℃; Zone 4: 180-190℃; Zone 5: 190-200℃; Zone 6: 200-205℃; and Zone 7: 200-205℃.
[0065] Example 4
[0066] (1) Mix 1200g of TPEE and 400g of Pebax evenly, then mix the resulting mixture with 10g of hindered amine light stabilizer 770 and 10g of Tinuvin 326 evenly, and then add 40g of reduced graphene oxide and mix until evenly dispersed.
[0067] (2) The material obtained in step (1) is added to a twin-screw extruder and melt-extruded at a temperature of 140-205℃ and a screw speed of 400rpm. Then the melt-extruded material is sequentially drawn, cooled, granulated and dried to obtain uniformly mixed granules. The granules are then injection molded, demolded and sized to obtain tower sealing material S4.
[0068] The seven heating zones of the twin-screw extruder are set with the following temperatures: Zone 1: 140-160℃; Zone 2: 160-170℃; Zone 3: 170-180℃; Zone 4: 180-190℃; Zone 5: 190-200℃; Zone 6: 200-205℃; and Zone 7: 200-205℃.
[0069] Example 5
[0070] (1) Mix 2000g of TPEE and 600g of Pebax evenly, and then mix the resulting mixture with 30g of hindered amine light stabilizer 770 and 20g of Tinuvin 326 evenly.
[0071] (2) The material obtained in step (1) is added to a twin-screw extruder and melt-extruded at a temperature of 140-205℃ and a screw speed of 400rpm. Then the melt-extruded material is sequentially drawn, cooled, granulated and dried to obtain uniformly mixed granules. The granules are then injection molded, demolded and sized to obtain tower sealing material S5.
[0072] The seven heating zones of the twin-screw extruder are set with the following temperatures: Zone 1: 140-160℃; Zone 2: 160-170℃; Zone 3: 170-180℃; Zone 4: 180-190℃; Zone 5: 190-200℃; Zone 6: 200-205℃; and Zone 7: 200-205℃.
[0073] Example 6
[0074] (1) Mix 2000g of TPEE and 200g of Pebax evenly, then mix the resulting mixture with 60g of hindered amine light stabilizer 770 evenly, then add 20g of multi-walled carbon nanotubes and 10g of reduced graphene oxide, and mix until evenly dispersed.
[0075] (2) The material obtained in step (1) is added to a twin-screw extruder and melt-extruded at a temperature of 140-205℃ and a screw speed of 400rpm. Then the melt-extruded material is sequentially drawn, cooled, granulated and dried to obtain uniformly mixed granules. The granules are then injection molded, demolded and sized to obtain tower sealing material S6.
[0076] The seven heating zones of the twin-screw extruder are set with the following temperatures: Zone 1: 140-160℃; Zone 2: 160-170℃; Zone 3: 170-180℃; Zone 4: 180-190℃; Zone 5: 190-200℃; Zone 6: 200-205℃; and Zone 7: 200-205℃.
[0077] Example 7
[0078] Prepared according to the method described in Example 1, except that in step (1), the amount of Pebax added is 900g, and tower sealing material S7 is obtained.
[0079] Example 8
[0080] Prepared according to the method described in Example 1, except that in step (1), the amount of Pebax added is 120g, and tower sealing material S8 is obtained.
[0081] Example 9
[0082] Prepared according to the method described in Example 1, except that in step (1), an equal amount of polyester block amide (purchased from Evonik Industries AG, brand name VESTAMID) was used. Ester X1033 was used instead of Pebax to obtain tower sealing material S9.
[0083] Comparative Example 1
[0084] Prepared according to the method described in Example 1, except that in step (1), the amount of Pebax added is 90g, and tower sealing material D1 is obtained.
[0085] Comparative Example 2
[0086] Prepared according to the method described in Example 1, except that in step (1), the amount of Pebax added is 1200g, and tower sealing material D2 is obtained.
[0087] Comparative Example 3
[0088] The tower sealing material D3 was prepared according to the method described in Example 1, except that an equal amount of silica was used instead of Pebax.
[0089] Test case
[0090] (1) The tower sealing material S4 prepared in Example 4 was tested by scanning electron microscopy. Figure 1 The scanning electron microscope image of the tower sealing material S4 is shown, which shows that graphene is uniformly dispersed in the polymer system, and the material has excellent uniformity.
[0091] (2) The tensile strength of the tower sealing materials prepared in the examples and comparative examples was tested using the method of GB / T 1040.2-2022. The results are shown in Table 1.
[0092] (3) The present invention uses the method of GB / T 16422.2-2022 to conduct xenon lamp aging tests on the tower sealing materials prepared in the examples and comparative examples, and calculates the tensile strength retention rate of the materials after xenon lamp aging for 1000h. The results are shown in Table 1.
[0093] in, Figure 2 The diagram shows the mechanical properties of the tower sealing material S5 prepared in Example 5 before and after aging. It can be seen that the mechanical properties of the sample after aging test did not decrease significantly, and the material has excellent weather resistance. Figure 3 The diagram shows the mechanical properties of the tower sealing material S6 prepared in Example 6 before and after aging. It can be seen that the mechanical properties of the sample after aging test decreased, but not by much, which meets the material requirements, indicating that the material prepared by this method also has good weather resistance.
[0094] (4) The surface resistivity of the tower sealing materials prepared in the examples and comparative examples was tested using the ASTM D257 method. The results are shown in Table 1.
[0095] (5) The initial decomposition temperature of the tower sealing materials prepared in the examples and comparative examples was tested by thermogravimetric analysis (TGA) in this invention. The results are shown in Table 1.
[0096] in, Figure 4 The thermogravimetric analysis results of the tower sealing material S3 prepared in Example 3 are shown. It can be seen that the material only decomposes significantly after 300°C, indicating that the material has excellent thermal stability.
[0097] Table 1
[0098]
[0099] As can be seen from the results in Table 1, the proposed design has excellent mechanical and antistatic properties, which are superior to the comparative examples. It is suitable for use as a sealing material in high-resolution, high-precision sensor systems for micro-leakage in petrochemical towers, ensuring the stability and accuracy of high-precision sensors.
[0100] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combining the various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A tower sealing material, characterized in that, The tower sealing material includes thermoplastic polyester elastomer, thermoplastic polyamide elastomer, light stabilizer, and optional nano-carbon material; wherein the weight ratio of the thermoplastic polyester elastomer to the thermoplastic polyamide elastomer is 2-15:
1.
2. The tower sealing material according to claim 1, characterized in that, Based on the total weight of the tower sealing material, the tower sealing material contains 50-90 wt% of the thermoplastic polyester elastomer, 5-40 wt% of the thermoplastic polyamide elastomer, 0.1-10 wt% of the light stabilizer and 0-5 wt% of the nano-carbon material.
3. The tower sealing material according to claim 1 or 2, characterized in that, The weight ratio of the thermoplastic polyester elastomer to the thermoplastic polyamide elastomer is 2.5-12:
1.
4. The tower sealing material according to any one of claims 1-3, characterized in that, The hardness of the thermoplastic polyester elastomer is 20-80D.
5. The tower sealing material according to any one of claims 1-3, characterized in that, The thermoplastic polyamide elastomer is selected from at least one of polyether block amide, polyester block amide, and polysiloxane block amide.
6. The tower sealing material according to claim 1, characterized in that, The light stabilizer is a combination of benzotriazole light stabilizers and hindered amine light stabilizers, and the weight ratio of the benzotriazole light stabilizer to the hindered amine light stabilizer is 1:0.1-10. Preferably, the benzotriazole light stabilizer is selected from at least one of 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-5-chlorobenzotriazole, 2'-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole, and 2,2'-methylene-bis[4-tert-octyl-6-(2H-benzotriazolyl-2)]phenol; Preferably, the hindered amine light stabilizer is selected from at least one of bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate, poly[1-(2-hydroxyethyl)-2,2,6,6-tetramethyl-4-hydroxypiperidinyl succinate] and poly{[6-[(1,1,3,3-tetramethylbutyl)amino]]-1,3,5-triazine-2,4-[(2,2,6,6-tetramethyl-piperidinyl)imino]-1,6-hexamethylene[(2,2,6,6-tetramethyl-4-piperidinyl)imino]}.
7. The tower sealing material according to claim 1, characterized in that, The nano-carbon material is selected from at least one of multi-walled carbon nanotubes, graphene, reduced graphene oxide, and carbon fiber.
8. A method for preparing the tower sealing material according to any one of claims 1-7, characterized in that, The method includes the following steps: (1) The thermoplastic polyester elastomer is mixed with the thermoplastic polyamide elastomer, and then the resulting mixture, the light stabilizer and the optional nano-carbon material are mixed together; (2) The material obtained in step (1) is added to a twin-screw extruder for extrusion and granulation to obtain granules. The granules are then injection molded, demolded, and sized.
9. The method according to claim 8, characterized in that, In step (2), the seven heating zones of the twin-screw extruder are set to the following temperatures: Zone 1: 140-160℃, Zone 2: 160-170℃, Zone 3: 170-180℃, Zone 4: 180-190℃, Zone 5: 190-200℃, Zone 6: 200-205℃, and Zone 7: 200-205℃.
10. The application of the tower sealing material according to any one of claims 1-7 in a high-resolution, high-precision sensor system for minor leaks in tower sealing.